2018
DOI: 10.3390/s19010087
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for Small UAV-Borne FMCW SAR

Abstract: Unmanned aerial vehicle borne frequency modulated continuous wave synthetic aperture radars are attracting more and more attention due to their low cost and flexible operation capacity, including the ability to capture images at different elevation angles for precise target identification. However, small unmanned aerial vehicles suffer from large trajectory deviation and severe range-azimuth coupling due to their simple navigational control and susceptibility to air turbulence. In this paper, we utilize the sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Over the Arctic, snow cover that can be characterized by a two-layer snowpack structure, and assumptions can be made on its mean refractive index, thereby allowing bulk SWE to be estimated (work in progress). Hu et al (2019) also showed the usefulness of imaging FMCW synthetic aperture radar onboard the RPA. Several studies have also shown the potential of FMCW radar for different applications, such as avalanche studies (Vriend et al, 2013;Okorn et al, 2014;Laliberté et al, 2021), snow stratigraphy based on successive FMCW echo analyses (Marshall and Koh, 2005;Marshall et al, 2007), snowpack tomography (Xu et al, 2018), and ice thickness monitoring (Yankielun et al, 1993;Gunn et al, 2015).…”
Section: Fmcw Radar (Fmcw-radar)mentioning
confidence: 93%
“…Over the Arctic, snow cover that can be characterized by a two-layer snowpack structure, and assumptions can be made on its mean refractive index, thereby allowing bulk SWE to be estimated (work in progress). Hu et al (2019) also showed the usefulness of imaging FMCW synthetic aperture radar onboard the RPA. Several studies have also shown the potential of FMCW radar for different applications, such as avalanche studies (Vriend et al, 2013;Okorn et al, 2014;Laliberté et al, 2021), snow stratigraphy based on successive FMCW echo analyses (Marshall and Koh, 2005;Marshall et al, 2007), snowpack tomography (Xu et al, 2018), and ice thickness monitoring (Yankielun et al, 1993;Gunn et al, 2015).…”
Section: Fmcw Radar (Fmcw-radar)mentioning
confidence: 93%
“…The returned signal from a point target whose nearest slant range is , can be written as: (4) where is the time delay, is the instantaneous slant range (ISR), is the speed of light, is the sum of the fast time / and slow time .…”
Section: A Stlfmcw Signal Modelmentioning
confidence: 99%
“…Unmanned aerial vehicle synthetic aperture radar (UAV SAR) is an advanced remote sensing technique that can obtain highresolution images with high efficiency and low energy consumption for many applications, such as search and rescue operations and civil infrastructure inspection missions [1][2][3]. However, because UAVs are lightweight and due to their aerodynamic mechanisms, the paths of UAVs are disturbed easily by the atmospheric turbulence, resulting in motion errors such as trajectory deviations and variations in velocity, and attitude [4]. Generally, synchronous navigation system measurements are used to acquire geometric information for motion compensation (MoCo).…”
Section: Introductionmentioning
confidence: 99%
“…However, spacevariant phase errors were not apparent. In [10], a method was proposed to deal with range-azimuth coupling using a squint minimization technique. Squinted Azimuth-dependent PGA and MEA were used as autofocus algorithms.…”
Section: Introductionmentioning
confidence: 99%